Response of plant-pollinator interactions to landscape transformations in the Greater Cape Floristic Region (GCFR) biodiversity hotspot - Adedoja, Opeyemi Adebayo (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhDAgric)--Stellenbosch University, 2019.